2003
DOI: 10.1074/jbc.m300180200
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Ca2+ Uptake Requires Sustained Ca2+ Release from the Endoplasmic Reticulum

Abstract: We analyzed the role of inositol 1,4,5-trisphosphateinduced Ca 2؉ release from the endoplasmic reticulum (ER) (i) in powering mitochondrial Ca 2؉ uptake and (ii) in maintaining a sustained elevation of cytosolic Ca 2؉ concentration ([Ca 2؉ ] c ). For this purpose, we expressed in HeLa cells aequorin-based Ca 2؉ -sensitive probes targeted to different intracellular compartments and studied the effect of two agonists: histamine, acting on endogenous H 1 receptors, and glutamate, acting on co-transfected metabotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 53 publications
(56 reference statements)
3
52
1
Order By: Relevance
“…Because the initial mitochondrial Ca 2ϩ transient remained unchanged even in the absence of extracellular Ca 2ϩ , it is tempting to speculate that this Ca 2ϩ spike is predominantly due to uptake of Ca 2ϩ released from the ER. Similar data have been described recently in HeLa cells (43). Our findings that histamine-initiated elevation in [Ca 2ϩ ] mito turned out to be long lasting when NCX mito was inhibited with CGP 37157 (44) is in line with reports demonstrating that NCX mito is the main mechanism of mitochondrial Ca 2ϩ extrusion in endothelial cells (37).…”
Section: Discussionsupporting
confidence: 81%
“…Because the initial mitochondrial Ca 2ϩ transient remained unchanged even in the absence of extracellular Ca 2ϩ , it is tempting to speculate that this Ca 2ϩ spike is predominantly due to uptake of Ca 2ϩ released from the ER. Similar data have been described recently in HeLa cells (43). Our findings that histamine-initiated elevation in [Ca 2ϩ ] mito turned out to be long lasting when NCX mito was inhibited with CGP 37157 (44) is in line with reports demonstrating that NCX mito is the main mechanism of mitochondrial Ca 2ϩ extrusion in endothelial cells (37).…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, it has been shown that Ca 2ϩ , which has been released from the ER by a continuous IP 3 generation, is sequestered by mitochondria and, thus, yields elevation in [Ca 2ϩ ] mito (40) (Fig. 7A).…”
Section: Discussionmentioning
confidence: 99%
“…Ca 2 þ influx from the cytosol to the ER lumen is mediated by the sarco/endoplasmic reticulum Ca 2 þ -ATPase (SERCA). 75,76 Fluctuations in Ca 2 þ concentration help regulate normal cell functions, 8 but ER Ca 2 þ imbalance and acute Ca 2 þ release from the ER lead to cell death. The aforementioned pump and channels at the ER membrane may, at least in part, control both of these conditions.…”
Section: Gangliosides and The Er Stress Responsementioning
confidence: 99%